Efek antibakteri dan antibiofilm minyak atsiri cendana india (santalum album l.) Terdahap fusobacterium nucleatum dan treponema denticola (in vitro) - Valeri, Clarissa; Tri Oka Binartha, Ciptadhi (Jurnal Kedokteran Gigi Terpadu, 2024)
Background: Periodontitis caused by pathogenic bacteria such as Fusobacterium nucleatum and Treponema denticola. Periodontitis prevented by chemical plaque control using chlorhexidine, but excessive chlorhexidine causes discoloration of the teeth. Indian sandalwood essential oil extract is a natural ingredient can be used as an alternative and have function inhibiting bacterial growth. Purpose: To determine the effect of Indian sandalwood essential oil in inhibiting the growth and biofilm of Fusobacterium nucleatum and Treponema denticola. Method: Fusobacterium nucleatum and Treponema denticola bacteria cultured at 37C for 24 hours. The 100% essential oil dissolved into concentrations 50%, 25%, 12,5%, 6,25%, 3,125%, 1,56%. Antimicrobial tests using microdilution method by calculating average colonies. Biofilm test using biofilm assay method with incubation period 1, 3, and 24 hours. Biofilm assay results viewed with a microplate reader with a wavelength 490 nm. Results: Microdilution of F. nucleatum and T. denticola obtained minimal inhibition at 50% concentration. Fusobacterium nucleatum biofilm test obtained inhibition at 50% concentration for 1 hour incubation period, while it can be killed at 50% concentration for 3 hours incubation and at 50%, 25%, 12,5%, 6,25% concentration for 24 hours incubation. Treponema denticola biofilm test obtained inhibition at 50% concentration for 1 and 3 hours incubation, while it can be killed at 50%, 25%, 12,5%, 6,25% concentration for 24 hours incubation. Conclusion: Indian sandalwood essential oil extract proved effective in inhibiting the growth and biofilm of F. nucleatum and T. denticola.